2016
DOI: 10.1016/j.neuroimage.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging on fronto-striatal reactive and proactive inhibitory control

Abstract: Inhibitory control, like most cognitive processes, is subject to an age-related decline. The effect of age on neurofunctional inhibition processing remains uncertain, with age-related increases as well as decreases in activation being reported. This is possibly because reactive (i.e., outright stopping) and proactive inhibition (i.e., anticipation of stopping) have not been evaluated separately. Here, we investigate the effects of aging on reactive as well as proactive inhibition, using functional MRI in 73 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 53 publications
(121 reference statements)
12
37
0
Order By: Relevance
“…5, 6; Tables 2–4) g,h,i and deactivation of, e.g., motor cortex in the reactive response inhibition network, as shown previously for the current task in young and older adults (Bloemendaal et al, 2016) and for similar paradigms (Zandbelt and Vink, 2010; Kleerekooper et al, 2016). …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…5, 6; Tables 2–4) g,h,i and deactivation of, e.g., motor cortex in the reactive response inhibition network, as shown previously for the current task in young and older adults (Bloemendaal et al, 2016) and for similar paradigms (Zandbelt and Vink, 2010; Kleerekooper et al, 2016). …”
Section: Resultssupporting
confidence: 82%
“…Two forms of response inhibition have been distinguished: reactive response inhibition is the process of canceling an ongoing response at the moment this is needed (i.e., outright stopping), whereas proactive response inhibition entails the preparation for stopping when this may become necessary, e.g., based on cues held in working memory. Age-related impairments have been shown in both reactive inhibition (measured with stop-signal reaction time; SSRT) and proactive inhibition (measured with anticipatory response slowing), particularly under high information load (i.e., high information processing demands for interpreting the stop-signal probability cues; Bloemendaal et al, 2016; Kleerekooper et al, 2016). It is unclear whether tyrosine-induced modulation of catecholaminergic signaling in older adults will affect reactive and/or proactive response inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…In behavioral studies, older adults have often been shown to exhibit longer stopping time, suggesting that there is an age-related inhibitory deficit (e.g., Kramer et al, 1994; Bedard et al, 2002; van de Laar et al, 2011; Kleerekooper et al, 2016). However, other studies found either no age-related decline (e.g., Kray et al, 2009) or only a specific deficit (e.g., Anguera and Gazzaley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is often associated with a decline in various executive functions (Hedden and Gabrieli, 2004; Gazzaley and D’Esposito, 2007; Levin and Netz, 2015) including memory, attention, reasoning abilities and inhibitory control (Fujiyama et al, 2012; Cuypers et al, 2013; Levin et al, 2014; Stewart et al, 2014; Bönstrup et al, 2015; McNab et al, 2015; Smittenaar et al, 2015; Cid-Fernández et al, 2016; Kleerekooper et al, 2016). Several hypotheses have been proposed emphasizing the possible relationship between these deficits and a progressive degeneration of the prefrontal cortex (Hedden and Gabrieli, 2004; Gazzaley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%